Nanotechnology-based strategies for effective delivery of phytoconstituents for the management of rheumatoid arthritis - Monika Joshi; Kamla Pathak; Suneela Dhaneshwar (Elsevier, 2022)
Rheumatoid arthritis [RA] is a painful disorder that causes inflammation in synovial membrane followed by damage to cartilage and bone. Several therapies are available for its management that include anti-inflammatory and disease- modifying antirheumatic drugs. Due to the severe side effects associated with them, phytotherapy may serve as a promising and beneficial approach for management of rheumatoid arthritis and the therapeutic potential can be attributed to their ability to target various inflammatory mediators including nitric oxide [NO], cytokines, chemokines, adhesion molecules, nuclear factor kappa-b [NF-kb], lipoxygenase [LOXs] and arachidonic acid [AA]. Further, nanomedicine could serve as a prominent formulation strategy to overcome the challenges associated with phytoconstituents like poor bioavailability, high first pass metabolism and lower stability. Present review focuses on providing an exhaustive account of various phytoconstituents that have significant potential in RA management, their drawbacks, reported novel drug formulations, regulatory aspects involved therein.